Appropriate technology and ethical obligations of the university: W.E.B. Du Bois on the Africana university mission†. Issue 4 (4th July 2017) - Verharen, C.; Kadoda, G.; Bugarin, F.; Fortunak, J.; Tharakan, J.; Schwartzman, D.; Wensing, E.; Middendorf, G.
Abstract : Working on the Encyclopedia Africana under the sponsorship of Kwame Nkrumah in Ghana, W.E.B. Du Bois reversed his conviction that only the 'talented tenth' could profit from a university education. He proposed that virtually all humans have a right to a university education. He further insisted that Africana (African and African in the Diaspora) universities are ethically obligated and uniquely positioned to spearhead a movement to train students to become professionals who solve problems community members are unable to solve for themselves. Africana universities can, with the aid of appropriate technology and service learning, take the steps necessary to achieve Du Bois's vision. In this paper, we present a practical account of how universities may work with local communities to determine the questions to research and then deploy appropriate technologies through community-based but student-driven service learning projects. Our hypothesis is that students can become community leaders of tomorrow by partnering with community members to solve theoretical issues and practical problems of their communities. As university graduates inspired by Du Bois's vision for Africana universities, their mission will be to establish alumni communities of learning that transfer problem-solving skills to community members who do not yet have access to university education.